ANALYSIS OF CULTURAL LITERACY ABILITY LEVEL OF 5TH GRADE STUDENTS IN SLEMAN DISTRICT ELEMENTARY SCHOOL.. - Disne, Maria Adventina; Rusmawan, Rusmawan; Susanti, Maria Melani Ika (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis research aims to determine the cultural literacy ability level of 5th grade elementary school students in the Sleman Sub-District. This research is a survey research with a population of 834 students from 9 schools. The researchers used 278 students of the population as the research sample. Researchers use the purposive sampling technique in the sampling process. Then the researchers used questionnaires and document studies as the research instruments. The data collected is analyzed descriptively. The results of this research indicate that the level of cultural literacy of students in Sleman District with the category of very high at 56 students (20.14%), high at 106 students (38.13%), medium at 94 students (33.81%), low at 22 students (7.19%), and very low 0 students (0.00). The cultural literacy of students in Sleman District is 106 (38.13%), which is indicated by the high indicators of cultural literacy. Keywords: cultural literacy, cultural literacy ability level.